2022
DOI: 10.1016/j.heliyon.2022.e08913
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and antioxidant activity of β-carotene loaded nanostructured lipid carrier (NLC) from binary mixtures of palm stearin and palm olein

Abstract: activity of β-carotene loaded nanostructured lipid carrier (NLC) from binary mixtures of palm stearin and palm olein, HELIYON, https://doi.org/10.1016/j.heliyon.2022.e08913. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Among these, it is important to remember that: the DPPH-antioxidant reaction is reversible to some extent; therefore, the measured antioxidant capacity may be lower than it should be; DPPH reagent shows low accessibility due to high steric hindrance; therefore, large molecules may not be able to access the DPPH radical site [ 24 ]. Some authors reported that the ABTS assay is more responsive than DPPH for the evaluation of the antioxidant activity of carotenoid extracts because ABTS correlates positively with their free radical scavenging activity compared to the DPPH assay [ 25 ]. All these considerations additionally support our DPPH results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, it is important to remember that: the DPPH-antioxidant reaction is reversible to some extent; therefore, the measured antioxidant capacity may be lower than it should be; DPPH reagent shows low accessibility due to high steric hindrance; therefore, large molecules may not be able to access the DPPH radical site [ 24 ]. Some authors reported that the ABTS assay is more responsive than DPPH for the evaluation of the antioxidant activity of carotenoid extracts because ABTS correlates positively with their free radical scavenging activity compared to the DPPH assay [ 25 ]. All these considerations additionally support our DPPH results.…”
Section: Resultsmentioning
confidence: 99%
“…SLN meet this need because they are composed of lipids, which are essential nutrients of the human diet and show good tolerability [ 38 ]. Lipid-based carriers are able to increase the bioaccessibility and the bioavailability of carotenoids [ 25 ]. In fact, nanoparticles can enhance carotenoid absorption by improving their solubility compared to the raw crystalline compound thanks to the greater surface-to-volume ratio, by prolonging the retention time, or through the direct absorption of the delivery systems.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, 1 mg/ml of NE_NLCs correspond to 0.208 ± 0.003 ng/ml of Trolox equivalent, while 1 mg/ml of NLCs to 0.054 ± 0.002 ng/ml of Trolox equivalent antioxidant capacity. The mild antioxidant activity of the bare NLCs is most probably due to the presence of oleic acid and glyceryl dibehenate, as already highlighted in the literature (Rohmah et al, 2022).…”
Section: Preparation and Characterization Of Nlcs And Ne_nlcsmentioning
confidence: 51%
“…In a previous report on co‐encapsulated liposomes of vitamin C and βC, the free radical scavenging rates of L‐VC‐βC, including DPPH, ABTS and OH radicals, were significantly higher than that of L‐βC, but had no significant difference from that of L‐VC 9 . In some other reports of βC loaded nanocarriers, for example, βC loaded nanostructured lipid carrier (NLC) from palm stearin and palm olein, fibre‐encapsulated carotene nanocapsules, only slight increases of radical scavenging rates were reported compared with unloaded βC 48,49 . Taken together, co‐encapsulation of VE and βC could improve the radical scavenging activities significantly, especially the combination at 5:3 with the highest antioxidant activities.…”
Section: Resultsmentioning
confidence: 88%
“…9 In some other reports of ⊎C loaded nanocarriers, for example, ⊎C loaded nanostructured lipid carrier (NLC) from palm stearin and palm olein, fibre-encapsulated carotene nanocapsules, only slight increases of radical scavenging rates were reported compared with unloaded ⊎C. 48,49 Taken together, co-encapsulation of VE and ⊎C could improve the radical scavenging activities significantly, especially the combination at 5:3 with the highest antioxidant activities.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 95%